Predictors of Self-Reported Hearing Problems Among Commercial Transport Workers Using Personal Listening Devices in Kano State, Nigeria: A Cross-Sectional Study - Abbas Muhammad Sani; Mamuda Alhaji Sabo; Alhassan Muhammad Baba; Umar Shuaibu; Aisha Aliyu Ibrahim; Faiza Mukhtar Uba Abubakar; Shafa'atu Kani Fago; Saminu Zakari Chiroma; Adamu Alhaji; Sani Abdullahi Giade; Ibrahim Shehu Aliyu; Aisha Mahmoud Ibrahim (West African Journal of Allied Health Sciences, 2026)
ABSTRACT Background Noise-induced hearing loss is one of the most common preventable occupational health problems worldwide. Commercial transport workers are routinely exposed to environmental and traffic noise and may experience additional auditory exposure through the use of personal listening devices. This study determined the prevalence of self-reported hearing problems and identified factors associated with hearing-related symptoms among commercial transport workers in Kano State, Nigeria. Methods A descriptive cross-sectional study was conducted among 410 commercial transport workers selected using a multistage sampling technique. Data were collected using a structured interviewer-administered questionnaire. Self-reported hearing problems were assessed based on the presence of hearing-related symptoms, including tinnitus, hearing difficulty, ear discomfort, and reduced hearing sensitivity. Data were analysed using IBM SPSS Statistics version 26. Associations were assessed using Pearson’s chi-square test, while multivariable logistic regression was performed to identify independent predictors of hearing problems. Adjusted odds ratios (aORs) with 95% confidence intervals (CIs) were reported. Statistical significance was set at p < 0.05. Results Self-reported hearing-related symptoms were common among respondents. Frequent need to increase listening volume was reported by 27.8%, ear discomfort by 25.9%, tinnitus by 23.9%, and difficulty hearing passengers or traffic sounds by 19.0%. Only 9.3% had ever undergone a formal hearing assessment. After adjustment for potential confounders, respondents aged above 30 years were more likely to report hearing problems (aOR = 1.82, 95% CI: 1.14–2.91, p = 0.012). Similarly, more than five years of occupational experience (aOR = 2.37, 95% CI: 1.43–3.92, p = 0.001), daily earphone use exceeding one hour (aOR = 2.69, 95% CI: 1.52–4.77, p < 0.001), listening at high volume (aOR = 3.14, 95% CI: 1.82–5.43, p < 0.001), earphone use while driving (aOR = 2.46, 95% CI: 1.41–4.31, p = 0.002), poor knowledge of hearing risks (aOR = 1.91, 95% CI: 1.12–3.27, p = 0.017), and failure to take listening breaks (aOR = 1.72, 95% CI: 1.01–2.93, p = 0.043) were independent predictors of hearing problems. Conclusion Hearing-related symptoms were common among commercial transport workers in Kano State and were significantly associated with both occupational and behavioural factors. Prolonged earphone use, high listening volume, earphone use while driving, poor hearing-risk awareness, and inadequate listening practices were important predictors of hearing problems. Occupational hearing conservation programmes, hearing-health education, and routine hearing screening should be prioritised among transport workers.